2010
DOI: 10.1111/j.1467-9450.2010.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents born extremely preterm: behavioral outcomes and quality of life

Abstract: Fifty-two extremely premature born and 54 full-term controls were assessed regarding behavioral outcomes, risk-taking and self-perceived quality of life. Behavioral outcomes were assessed with the Achenbach Youth Self Report; risk-taking was estimated regarding alcohol and nicotine use; self-perceived quality of life and future expectations were rated; and attention and hyperactivity problems were surveyed retrospectively with the Wender Utah Rating Scale. The prematurely born reported fewer problems than full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 42 publications
5
28
1
1
Order By: Relevance
“…One possibility is that their executive function deficits do not influence daily life functioning. Other studies have reported similar results on self-report in VLBW groups as in controls, even though their parents reported increased symptoms in adolescence (Grunau, Whitfield, & Fay, 2004;Hack et al, 2004;Hallin & Stjernqvist, 2011;Indredavik, Vik, Heyerdahl, Kulseng, & Brubakk, 2005;Saigal et al, 2003). Another possible interpretation is that they are underreporting their struggles, due to lack of insight regarding own functioning, which has been reported by others (Knight, Rutterford, Alderman, & Swan, 2002).…”
Section: Discussionsupporting
confidence: 52%
“…One possibility is that their executive function deficits do not influence daily life functioning. Other studies have reported similar results on self-report in VLBW groups as in controls, even though their parents reported increased symptoms in adolescence (Grunau, Whitfield, & Fay, 2004;Hack et al, 2004;Hallin & Stjernqvist, 2011;Indredavik, Vik, Heyerdahl, Kulseng, & Brubakk, 2005;Saigal et al, 2003). Another possible interpretation is that they are underreporting their struggles, due to lack of insight regarding own functioning, which has been reported by others (Knight, Rutterford, Alderman, & Swan, 2002).…”
Section: Discussionsupporting
confidence: 52%
“…In general, young adults born preterm have not rated their HRQoL significantly differently from normal birthweight peers, but there have been few studies limited to EPB subjects, both for adolescents (3,9) and young adults (10)(11)(12). We are not aware of any studies on how perception of different aspects of HRQoL may change from adolescence to adulthood.…”
Section: Introductionmentioning
confidence: 98%
“…A systematic review identified that premature children in preschool and school had worse quality of life indexes than full-term infants (Vieira & Linhares, 2011). However, in adolescents and adults, the effects of prematurity and low birth weight on quality of life decreased with age, and the difference between full-term and premature birth was not maintained; this finding suggests that an adaptation process occurs over time (Hallin & Stjernqvist, 2011).…”
mentioning
confidence: 82%